STRATEGIES FOR EFFECTIVE TEACHING OF READING AMONG SECONDARY SCHOOLS IN MORO LOCAL GOVERNMENT AREA OF KWARA STATE - saliu, kolawole (UPT. Pengembangan Bahasa IAIN Zawiyah Cot Kala Langsa, 2019)
Learning a language is different from acquiring it. To learn a language, all necessary skills are required. However, reading, a receptive skill, remains one of those four skills needed for language learning. As teachers of English, all efforts must be put forward in order to improve the teaching of reading through required strategies for effective teaching. This study however centers on effective teaching strategies of reading among secondary schools in Moro Local Government Area of Kwara State. In order to achieve this, questionnaire was used to elicit information on the respondents so as to be able to gather all necessary information needed for this study. The sample consists of Sixty (60) English language teachers who were randomly selected across twenty (20) randomly selected Junior and senior secondary schools in Moro Local Government Area of Kwara State. Data were analysed using descriptive and correlation statistics. The findings of the study revealed that the use of flash-cards, passage of relevant pictures and photographs, among others, are the teaching strategies needed for effective teaching of reading. Based on the result of the findings, it was recommended that sufficient teaching materials should be provided by government to assist teachers in the teaching of reading. This, among others, were discussed in this study.